FROM LOCAL TO GLOBAL: REINVENTING LOCAL LITERATURE THROUGH ENGLISH WRITING CLASSES - Ahmad Chaedar Alwasilah (TEFLIN Journal: A publication on the teaching and learning of English, 2006)
Abstract: Many do not realize that the current practice of teaching English in Indonesia has overlooked the function and potential of local literature. Being a multicultural country, Indonesia is rich in ethnic and minority literature to contribute to the world. However, due to misconceptions among Indonesian educators and decision makers, consciously or unconsciously this local geniusÃÂ has long been marginalized and less appreciated. In many English departments, for example, its value and significance has been underestimated. A survey of collaborative writing classes in English Department of UPI has revealed that the students positively responded the Sundanese literature-based writingÃÂ courses. The course was successful in two ways: developing writing skills through collaborative workshop and raising awareness of their own ethnic literature, which is a bridge to appreciate English literature.